2001
DOI: 10.1021/ic0103493
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Coordination Properties of New Bis(phosphinomethyl)pyridine N,P,P‘-Trioxides

Abstract: In a search for more hydrocarbon solvent soluble derivatives of the parent ligand, 2,6-[Ph(2)P(O)CH(2)](2)C(5)H(3)NO (1a), a series of new ligands, 2,6-[R(2)P(O)CH(2)](2)C(5)H(3)NO [R = Bz (1b); Tol (1c); Et (1d); Pr (1e); Bu (1f); Pn (1g); Hx (1h); Hp (1i); and Oct (1j)] and 2,6-[RR'P(O)CH(2)](2)C(5)H(3)NO [R = Ph, R' = Bz (2a); R = Ph, R' = Me (2b); R = Ph, R' = Hx (2c); R = Ph, R' = Oct (2d)], have been prepared by either Arbusov or Grignard substitutions on 2,6-bis(chloromethyl)pyridine followed by N-oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
61
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 13 publications
12
61
0
Order By: Relevance
“…For example, the tris-heterocyclic ligand, 2,2':6',2''-terpyridine (terpy), and its numerous derivatives represent one of the most widely investigated classes of chelating ligands used in coordination chemistry [1][2][3][4][5]. Another widely studied class of tris-heterocyclic ligands is the 2,6-In recent contributions we have described several new multidentate phosphine oxide ligands based upon pyridine and pyridine N-oxide platforms including ligands of types E-I, as shown in Figure 1, and their coordination chemistry with f-element ions has proven to be interesting [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In particular, the Noxide ligands, E and G (designated as NOPO) and I (designated as NOPOPO) appear to bind more effectively with lanthanide [Ln(III)] cations than their pyridine analogs F and H, and the more flexible ligands of types G and I coordinate more strongly than ligands of type E despite the larger chelate ring ray diffraction methods.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the tris-heterocyclic ligand, 2,2':6',2''-terpyridine (terpy), and its numerous derivatives represent one of the most widely investigated classes of chelating ligands used in coordination chemistry [1][2][3][4][5]. Another widely studied class of tris-heterocyclic ligands is the 2,6-In recent contributions we have described several new multidentate phosphine oxide ligands based upon pyridine and pyridine N-oxide platforms including ligands of types E-I, as shown in Figure 1, and their coordination chemistry with f-element ions has proven to be interesting [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In particular, the Noxide ligands, E and G (designated as NOPO) and I (designated as NOPOPO) appear to bind more effectively with lanthanide [Ln(III)] cations than their pyridine analogs F and H, and the more flexible ligands of types G and I coordinate more strongly than ligands of type E despite the larger chelate ring ray diffraction methods.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It had been further demonstrated that one derivative with R = 2-ethyl hexyl (EtHx) (1a) groups had superior extraction performance features compared to the well known CMPO extractants. Therefore, the initial objective involved development of a general scaled-up synthesis procedure for 1a and new derivatives.…”
Section: Nopopo Ligand Developmentmentioning
confidence: 99%
“…During Year 1 of the project, this goal was achieved by using a Grignard-based synthesis variation used to prepare the derivative with R = Ph 1 . Sample runs that produced in excess of 25 g of 1a were accomplished and plans were made for further scale-up (not an entirely routine task in an academic research lab setting).…”
Section: Nopopo Ligand Developmentmentioning
confidence: 99%
“…The phases were separated and the organic phase dried over MgSO 4 . The solvent was then vacuum evaporated leaving a yellow oil (1.4 g) that was purified by column chromatography (silica gel 70-230 mesh, CH 2 Cl 2 :MeOH 8:1) from which a white powder (11) 2,6-Bis(N,N-dimethylpropionamide)pyridine N-oxide (12). A suspension of 11 (500 mg, 1.8 mmol), NaHCO 3 (0.31 g, 3.75 mmol) and OXONE (800 mg, 1.29 mmol) in water (2.7 mL) and MeOH (8.5 mL) was stirred under nitrogen at 45-50°C (24 h).…”
Section: -(Nn-dimethylpropionamide)pyridine (9)mentioning
confidence: 99%